Las negociaciones sobre armas pequeñas: una visión histórica - Arce Mora, María Angélica (Revista Mexicana de Política Exterior, 2022)
This article deals with the stockpiling of small arms and light weapons worldwide and the negotiations that have taken place since the mid-nineties on an international, regional and sub-regional level to address the problem. One of these rounds of negotiations resulted in the adoption of the OAS Inter-American Convention Against the Manufacture and Illicit Trafficking of Firearms, Munitions, Explosives and Related Materials, which came into effect on the first of July, 1998, while the first and second Intergovernmental Groups of Experts on Small Arms came up with measures to prevent the use of these types of weapons and reduce stockpiles. Similarly, the author highlights the most relevant aspects of the Program of Action, adopted by the UN Conference on the Illicit Trade in Small Arms and Light Weapons in all its Aspects, which drew the world’s attention to the problem and which proposes measures to combat it on a national, regional and international level. According to Arce Mora, Mexico has actively participated in all these efforts and in parallel negotiations, and we can hope to see the delegations to the UN, including that of Mexico, assume a more active position with regard to this issue. The report that is to be put to the consideration of the UN General Assembly in 2007 will also be of great significance. The author concludes by acknowledging the participation of NGOs and civil society in efforts to prevent the use and stockpiling of small arms and light weapons.